Mass transfer and reaction kinetics of soybean oil epoxidation in a formic acid‐autocatalyzed reaction system. (17th June 2016) - Wu, Zhenyu; Nie, Yong; Chen, Wei; Wu, Lihang; Chen, Ping; Lu, Meizhen; Yu, Fengwen; Ji, Jianbing
Abstract : In this study, the mass transfer and reaction kinetics of soybean oil epoxidation using concentrated hydrogen peroxide in a formic acid‐autocatalyzed reaction system were studied in detail. Studying the mass transfer of formic acid showed that the influence of reactant diffusion near the interface is eliminated when the stirring rate is > 120 rpm in a double‐stirred cell, and the mass transfer rate decreases greatly with the conversion of double bonds and a decrease of reaction temperature. A temperature increase has little impact on the equilibrium of formic acid in the oil/water system, while an increase of epoxidized soybean oil significantly increases the value of the partition coefficient of formic acid. Another important aspect in the kinetic study is the decomposition of performic acid, which can cause the reduction of H2 O2 and formic acid during the reaction. Finally, a biphasic model, which considers all reactions in oil and aqueous phases, the equilibrium and mass transfer of reagents and products between the phases, and the evolution of proton concentrations with time, was developed to describe the epoxidation process.